MEMBENTUK KARAKTER ISLAMI DI ERA DIGITAL:PELAJARAN MORAL DARI AL QUR'AN: Membentuk Karakter Islam di Era Digital: Pelajaran Moral dari Al-Qur'an - Moh. Akib (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2025)
The digital age continues to advance quickly, and because of that, people need to deal with many situations that contain moral value problems that have never happened before. Due to the unlimited use of social media and technology, human interactions, communication, and business practices are changing, the change creating a new environment that often needs to make a different moral position. The moral value mentioned earlier, like amanah (responsibility), sidq (honesty), and adab (ethics), among other moral principles provided in the Qur'an, needs further attention in this circumstance digital era as the foundation of both individual and group daily behavior. In a digital world that is always evolving, the question of how to apply these ideas effectively emerges. With the help of responsible technology principles, this essay seeks to investigate how the values of amanah, sidq, and adab might be applied in a digital setting. The research's primary goal is to demonstrate how the lesson from the Qur'an can give practical solutions who can adapt to daily life to encounter moral challenges in the digital age and also strengthen the integrity of individuals and society especially the younger generation. This research's methodology consists of a literature review that discusses character development in the digital age as well as a thematic analysis of Qur'anic verses that contain moral values like amanah, sidq, and adab. According to preliminary research, applying the teachings of the Qur'an, especially in the areas of amanah, sidq, and adab can improve a person's moral integrity. Then, keeping morals and responsible individuals in the digital environment can have a positive effect on society. In conclusion, the application of these teachings from the Qur'an can provide a solid moral foundation for overcoming the difficulties presented by digital technology